Investigating Online Collaborative Grammar Learning Via Google Docs and Whatsapp: Indonesian EFL Undergraduate Students Views - Febriyanti, Rina Husnaini; Sundari, Hanna; Baron, Rifari; Arfani, Sri (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Acquisition of grammar is essential in English instruction because it is the foundation of learning its language, yet EFL learners often face obstacles, particularly in online settings. At the same time, recently, technology has rapidly embraced and offered various platforms or applications as learning aids in the English education field. The incorporation of technology facilitation is believed to boost the student’s grammar competency. However, the delving of students’ views of grammar learning online and collaboration is still infrequent. In an attempt to fill the gap, the current study investigated the students’ views on utilizing Google Docs and WhatsApp in online collaborative grammar learning. This descriptive qualitative case study examined 99 participants consisting of 17 males and 82 females of Indonesian EFL undergraduate students at a private university in Jakarta, Indonesia, who viewed Google Docs and WhatsApp in online collaborative grammar learning. The data was collected by questionnaire and interview and then analyzed descriptively. The findings revealed that the students' views positively influenced their substantive feelings, collaboration, teamwork skills, confidence, autonomy, and self-regulation. Grounded by the findings, the current paper illustrates recommendations for conducting online collaborative grammar learning integrated with Google Docs and WhatsApp for the learner and the instructor in preparing a syllabus and technical procedure. The result of the current study implied that both the platform and application offer the potential to be adopted in online or hybrid collaboration instruction.